An exploratory study of end‐of‐life prognostic communication needs as reported by widowed fathers due to cancer. Issue 11 (6th February 2015) - Park, Eliza M.; Check, Devon K.; Yopp, Justin M.; Deal, Allison M.; Edwards, Teresa P.; Rosenstein, Donald L.
Abstract: Objective: Effective physician communication about prognosis is a critical aspect of quality care for families affected by terminal illness. This is particularly important for spousal caregivers of terminally ill parents of dependent children, who may have unique needs for communication about anticipated death. The objective of this study was to explore end‐of‐life prognostic communication experiences reported by bereaved fathers whose wives died from cancer. Methods: From October 2012 to November 2013 we surveyed widowed fathers whose wives died from cancer through an open‐access educational website. The survey included the following open‐ended questions regarding prognostic communication: ' What is the most important thing you would like us to know about whether/how your wife's doctors communicated with you about her anticipated death? What do you wish had been different, if anything? ' We performed traditional content analysis of responses. Two researchers coded and categorized the data. Results: Two hundred forty‐four men responded to the survey questions on prognostic communication. Major themes addressed by respondents were the importance of clear and honest communication and physician bedside manner. They also identified unmet information needs, including wanting to know prognosis sooner. Relevant sub‐themes included death coming as a surprise, avoidance, and caregiver regret. Conclusions: Surviving spouses due to cancer can provide important insights for health care providers about optimum prognostic communication at the end of life. Increased physician attention to the communication preferences of both patients and their partners may improve bereavement outcomes for family members. Copyright © 2015 John Wiley & Sons, Ltd.